Engineering mechanics dynamics - Meriam, J. L. (John Wiley & Sons, 2013)
The latest edition of Engineering Mechanics-Dynamics continues to provide the same high quality material seen in previous editions. It provides extensively rewritten, updated prose for content clarity, superb new problems in new application areas, outstanding instruction on drawing free body diagrams, and new electronic supplements to assist learning and instruction.